2015
DOI: 10.1073/pnas.1424869112
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3Bexpression in breast cancer reflects cellular proliferation, while a deletion polymorphism is associated with immune activation

Abstract: Genomic sequencing studies of breast and other cancers have identified patterns of mutations that have been attributed to the endogenous mutator activity of APOBEC3B (A3B), a member of the AID/APOBEC family of cytidine deaminases. A3B gene expression is increased in many cancers, but its upstream drivers remain undefined. Furthermore, there exists a common germ-line deletion polymorphism (A3B del ), which has been associated with a paradoxical increase in breast cancer risk. To examine causes and consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
122
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 61 publications
17
122
4
Order By: Relevance
“…It is possible that downregulation of APOBEC3B and a subsequent decrease in tumor evolution through lowered mutation rates may also contribute to these encouraging clinical responses. Based on substantive prior work from our lab and others demonstrating a major role for APOBEC3B in cancer mutagenesis and correlating high levels of APOBEC3B with poor prognoses for ER-positive breast cancers (46,47), together with the studies presented here, we propose that existing inhibitors of the PKC-NFκB axis such as AEB071 may be repurposed to treat primary tumors in combination with existing therapies and help prevent detrimental outcomes such as drug resistance and metastases.…”
Section: Discussionsupporting
confidence: 61%
“…It is possible that downregulation of APOBEC3B and a subsequent decrease in tumor evolution through lowered mutation rates may also contribute to these encouraging clinical responses. Based on substantive prior work from our lab and others demonstrating a major role for APOBEC3B in cancer mutagenesis and correlating high levels of APOBEC3B with poor prognoses for ER-positive breast cancers (46,47), together with the studies presented here, we propose that existing inhibitors of the PKC-NFκB axis such as AEB071 may be repurposed to treat primary tumors in combination with existing therapies and help prevent detrimental outcomes such as drug resistance and metastases.…”
Section: Discussionsupporting
confidence: 61%
“…In some samples, up to 70% of all mutations are associated with the APOBEC mutational signature (Supplemental Table 1), confirming that APOBEC mutagenesis may be an important factor for cancer progression and tissue transformation (de Bruin et al 2014;Henderson et al 2014;McGranahan et al 2015). Recently, it was shown that the expression level of APOBEC3B has prognostic potential, and APOBEC was suggested as a target for oncotherapy (Cescon et al 2015).…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, elevated levels of APOBEC3B mRNA have been shown to associate with cellular proliferation, whereas the APOBEC3B deletion polymorphism associated with activation of immune-related genes [16]. Interestingly, increased lymphocytic infiltration has been associated with a favorable outcome in some, but not all subtypes of breast cancer [34,35].…”
Section: Discussionmentioning
confidence: 99%